THE MAPPING OF LOCAL ECONOMIC DEVELOPMENT IN DECENTRALIZED GOVERNANCE ERA - Hermien Triyowati (Universitas Trisakti, 2011)
This paper summarizes the relationship between decentralized governance and local economics development, and the mapping of LED’s concept at the country that implemented decentralized governance model. This paper seeks to (a) Understand what is the LED’s concept compare with the Decentralized Government for Development (DGD) concept, (b) Describe the impact ofthe DGD’s implementation in Indonesia base on the past research from some experts; and (c) Informing some comprehensive program and projects which better be conducted for to reach the main goal of MDGs: eradicate poverty.As a relatively new literature overview, the paper thus grapples with the many research or empiric experience conducted by many expert some time ago, and concludes with three prerequisite in implemented the LED’s concept was combined with DGD’s concept which is expected will be able to add the understanding about local economics development concept at the government that applying decentralized governance model.